The trial of General Homma : truth about the Japanese atrocities in the Philippines. - Angeles, Irineo B. (n.p)
Reprinted from Chronicle Magazine, May 8, 1965
Keywords: Philippines -- History -- Japanese occupation, 1942-1945; Homma, Masaharu, Lt. Gen. of the Japanese Imperial Army